Білоконенко Л. А. Українськомовний міжособистісний конфлікт - Іващенко, В. (Мовознавство, 2016)
Рецензія на книгу: Білоконенко Л. А. Українськомовний міжособистісний конфлікт. К. : Інтерсервіс, 2015.— 335 с.